PERBEDAAN KECERDASAN EMOSIONAL DAN HASIL BELAJAR BIOLOGI SISWA ANTARA YANG DIAJAR MELALUI MODEL PEMBELAJARAN BERBASIS PROYEK DENGAN MODEL PEMBELAJARAN LANGSUNG - Sri Rahayu Ilyas (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
The study aims at axamining the differences of emotional intelligence and students learning result on Biology subject between the ones who taught by employing Project-based learning model on environmental pollution lesson material in SMAN 5 Pinrang. The study is a quasi-experimental research with pretes-posttest only non-equivalen control group design. Sample was taken by employing random sampling technique, which obtained grade X IPA1 as the experiment class and grade X IPA2 as the contol class. Data were collected by using pretest and posttest of emotional intelligence and students learning result instrument. Data were analyzed using t-test. The result of the study revealed that 1) Students emotional intelligence taught by employing project-based learning model were different significantly between the ones taught by employing direct learning model with the mean 112,34 and 107,38 respectively, 2) Student learning result on Biology subject were different significantly between the ones taught by employing project-based learning model and direct learning model with the mean 89,19 and 86,09 respectively.